THE INFLUENCE OF SPENDING HABITS, SPIRITUAL INTELLIGENCE, AND FINANCIAL LITERACY ON THE FINANCIAL MANAGEMENT OF STUDENTS (CASE STUDY OF AR-ROYAN BAITUL HAMDI STUDENT BOARDING SCHOOL YOGYAKARTA) - Awwal, Muhammad Al Faridho; Agustina, Titana Diva (International Journal of Business, Law, and Education, 2023)
This research was conducted to examine the effect of spending habits, spiritual quotient, and financial literancy to financial management of Pondok Pesantren Mahasiswa (PPM) Ar-Royyan Baitul Hamdi Yogyakarta students. The population in this study were sutend of Pondok Pesantren Mahasiswa (PPM) Ar-Royyan Baitul Hamdi Yogyakarta students with samples taken using simple random sampling. Primary data collecting by distributing questionners. There are 150 quietionnaires processed in this study. The data analysis in this study used. The data analysis in this study used multiple linear regression analysis using SPSS software to test the research data. The result shows. The result showed that spending habits, spiritual quotient, and financial literation simultaneously has a significant effect on financial management of Pondok Pesantren Mahasiswa (PPM) Ar-Royyan Baitul Hamdi Yogyakarta students. Partially, the spending habits variable does not have a significant effect on financial management students of Pondok Pesantren Mahasiswa (PPM) Ar-Royyan Baitul Hamdi Yogyakarta with a significant level of 0.121 above 0.05. The spiritual quotient variable has a significant negative effect on financial management student of Pondok Pesantren Mahasiswa (PPM) Ar-Royyan Baitul Hamdi Yogyakarta with a significant level of 0.708 above 0.05. The financial literacy variable has a positif significant effect on financial manaement Pondok Pesantren Mahasiswa (PPM) Ar-Royyan Baitul Hamdi Yogyakarta students with a significant level of 0,000 below 0,05. Spending habits have no effect and are not significant on the financial management of students at the Ar-Royan Baitul Hamdi Yogyakarta Islamic Boarding School (PPM). Furthermore, spiritual intelligence has a negative and insignificant effect on the financial management of students at the Ar-Royan Baitul Hamdi Yogyakarta Islamic Boarding School (PPM). Furthermore, financial literacy has a positive and significant effect on the financial management of Yogyakarta PPM students. The students of the Ar-Royyan Baitul Hamdi Yogyakarta Islamic Boarding School (PPM) are expected to be more able to hold back from doing consumptive things